Chemical composition, pretreatments and saccharification of Senna siamea (Lam.) H.S. Irwin & Barneby: An efficient biomass producing tree legume. (May 2016) - Mund, Nitesh K.; Dash, Debabrata; Barik, Chitta R.; Goud, Vaibhav V.; Sahoo, Lingaraj; Mishra, Prasannajit; Nayak, Nihar R.
Highlights: A novel legume tree " Senna siamea " producing high biomass was identified. Glucan, hemicellulose and lignin contents of the biomass analysed. The 2 years old coppice biomass contains 39.59% fermentable glucose. COSLIF pretreatment found to be more efficient than alkali in releasing glucose. Using the glucose released (%), theoretical ethanol yield was calculated. Abstract: Protocols were developed for efficient release of glucose from the biomass of Senna siamea, one of the highly efficient biomass producing tree legumes. Composition of mature, 1 year and 2 years coppice biomass were analysed. For the hydrolysis of the glucan, two pretreatments, cellulose solvent- and organic solvent-based lignocellulose fractionation (COSLIF) and alkali (sodium hydroxide) were used; COSLIF (85% phosphoric acid, 45 min incubation at 50 °C) pretreated mature biomass exhibited best result in which 88.90% glucose released after 72 h of incubation with the use of 5 filter paper units (FPU) of cellulase and 10 international units (IU) of β -glucosidase per gram of glucan. Of the biomass of different particle sizes (40–200 mesh) used for saccharification, 40–60 mesh shown the maximum glucose release. COSLIF pretreated mature, 1 year and 2 years coppice biomass showed equivalent glucose release profiles.